Diseño de Herramientas Enfocadas a Empleados y Clientes: Plan de Mejora Gallagher Colombia–Bogotá (2021)
Through this work I want to publicize the process, learning and realization of the professional internships to be carried out in Gallagher Colombia at the Bogotá headquarters, the department where the tasks and activities were carried out was in Customer Service and Profits. The company has three lines of business which are insurance brokerage, insurance brokerage, reinsurance and consulting, in the line where the activities were carried out was in brokerage of insurance. It is a very humanistic, comprehensive company and works to break down barriers from the core that are the employees, providing a good work environment, creating ties with the customers and generating confidence to continue impacting markets. Therefore, this work shows the improvement plan that was carried out to create that familiarity with customers and employees to ensure growth in the Colombian market since the company has been in the country for a few years.